2014
DOI: 10.1142/s2010324714500052
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Spin Waves in Graphene Structures

Abstract: Basing on Dirac equation for interacting massless fermions, we propose a nonlinear model that describes a possible mechanism of ferromagnetism in graphene structures, resulting from electronelectron interaction and spontaneous breaking of spin symmetry of valence electrons. Qualitative predictions of the model are important for practical applications in spintronics. Localized kinkantikink patterns of valence electron spin density on the graphene surface are calculated, their interaction is described, and,¯nall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 27 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Evidently, in the articles [1,[4][5][6][7][8], it is shown that the density of spin symmetry was broken by the spontaneous breaking, which obeyed a nonlinear equation, and the offered nonlinear models with the limits will exist exact and approximate solutions for the distribution of the spin density and magnetization on the surface of the graphene structures, as the method of the scattering matrix [5]; the finite element method (FEM) and the Ritz method [1,7]; the Ritz method using Hermitian functions as coordinate functions [8].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidently, in the articles [1,[4][5][6][7][8], it is shown that the density of spin symmetry was broken by the spontaneous breaking, which obeyed a nonlinear equation, and the offered nonlinear models with the limits will exist exact and approximate solutions for the distribution of the spin density and magnetization on the surface of the graphene structures, as the method of the scattering matrix [5]; the finite element method (FEM) and the Ritz method [1,7]; the Ritz method using Hermitian functions as coordinate functions [8].…”
Section: Introductionmentioning
confidence: 99%
“…This model describes experimentally observable ferromagnetic properties of such films; prior work [6] claimed that the offered variant of the nonlinear field model, in which carriers of spin density are not fermions (electrons), but bosons (spinons), is quite adequate for describing the magnetic properties of graphene structures. The authors proposed in two articles [1,7] the desirability of a nonlinear model that describes a possible mechanism of ferromagnetism in graphene structures, resulting from electron-electron interaction and spontaneous breaking of spin symmetry of valence electrons. We investigated such spatially localized nonlinear spin of the valence electron density on the graphene surface such as kinks, and their interactions, as well as quasibound metastable states of the interacting kinks and antikinks, that are breathers [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations